Teaching English at Primary School: Will It Threaten The Growth of Students' Nationalism Feeling? (NOBEL: Journal of Literature and Language Teaching, 2017)
There is a fear that teaching foreign language to primary school students may distract the growth of nationalism feeling of the students. It is due to the fact that children within 6 to 12 years old are vulnerable. They are easy to be influenced or shaped by other cultures. Within this age, they are still in the process of developing themselves, in the aspect of personality and social life. However, research conducted on this matter does not prove that teaching foreign language to primary school students can obstruct the growth of students' nationality feeling. The aim of this article is to present literature review related to the questions whether teaching English as a foreign language may distract students' growth of nationality feeling. Then it goes further on the explanation on the requirements that policy maker must prepare when deciding to include English lesson as one of the subjects taught at primary school level.